Unilateral Thalamic Venous Infarction in an Infant: A Rare Presentation of Bilateral Deep Cerebral Venous Thrombosis - Katherine Chung; Umar Tariq; Rabia M. Khan; Thomas P. Nickles; Joseph H. Lock (Case Reports in Radiology)
Cerebral venous thrombosis (CVT) may manifest as superficial cerebral venous thrombosis (SCVT) or deep cerebral venous thrombosis (DCVT). Of the two patterns, DCVT is less commonly observed, although it often results in greater morbidity and mortality due to involvement of the deep gray nuclei. It can present at any age and typically results in edema of the bilateral thalami, with occasional extension into the basal ganglia. Unilateral thalamic infarct is rare and results in an ambiguous imaging pattern. We present the clinical and neuroimaging profile of an acute unilateral thalamic venous infarct in an infant secondary to bilateral DCVT. Early recognition of this atypical pattern will facilitate accurate diagnosis and treatment, and obviate the need for unnecessary interventions.